2018
DOI: 10.1093/jmcb/mjy025
|View full text |Cite
|
Sign up to set email alerts
|

A novel long non-coding RNA Myolinc regulates myogenesis through TDP-43 and Filip1

Abstract: Myogenesis is a complex process required for skeletal muscle formation during embryonic development and for regeneration and growth of myofibers in adults. Accumulating evidence suggests that long non-coding RNAs (lncRNAs) play key roles in regulating cell fate decision and function in various tissues. However, the role of lncRNAs in the regulation of myogenesis remains poorly understood. In this study, we identified a novel muscle-enriched lncRNA called 'Myolinc (AK142388)', which we functionally characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 69 publications
4
65
0
Order By: Relevance
“…Previous studies have shown that TDP43 promotes MYOD expression by directly binding to its promoter in C2C12 cells [32]. In the present study, TDP43 was also enriched in the promoter of MYOD in PSCs through the CHIP experiment, indicating the same mechanism in mice and pigs ( Figure 4A).…”
Section: H19 Regulates Psc Differentiation By Affecting the Enrichmensupporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies have shown that TDP43 promotes MYOD expression by directly binding to its promoter in C2C12 cells [32]. In the present study, TDP43 was also enriched in the promoter of MYOD in PSCs through the CHIP experiment, indicating the same mechanism in mice and pigs ( Figure 4A).…”
Section: H19 Regulates Psc Differentiation By Affecting the Enrichmensupporting
confidence: 78%
“…Among the different proteins detected by MS, TDP43 attracted our attention the most. TDP43, as a RNA/DNA binding protein, plays an important role in myoblast differentiation [32]. Western blot analysis was carried out to validate the interaction between H19 and TDP43 ( Figure 1B).…”
Section: H19 Physically Interacts With Tdp43mentioning
confidence: 99%
“…PPARA is activated by endogenous fatty acid metabolite ligands in response to fasting and promotes the uptake, utilization, and catabolism of fatty acids by regulating a wide range of genes that reprogram metabolic pathways to facilitate the use of lipids as an energy source. The direct regulation of protein-coding genes by PPARA is well characterized, but it was not known whether lncRNAswhich may influence gene expression through a variety of mechanisms Militello et al, 2018;Zhao et al, 2016) -also serve as direct targets contributing to physiological changes induced by PPARA activation. This possibility was suggested by the finding that several hundred liver-expressed lncRNAs are dysregulated in livers exposed to xenobiotic agonist ligands of the nuclear receptors CAR and PXR (Lodato et al, 2017), which contribute to the regulation of lipid metabolism and whose gene targets overlap with those of PPARA (Cui and Klaassen, 2016;Wada et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…41 In addition to the above ceRNA mechanism, some lncRNAs regulate gene expression in cis or trans. 45 Overexpression of lncRNA MyoD upstream non-coding (MUNC) induced from a heterologous promoter increased endogenous MyoD, MyoG and Myh3 mRNA, but not protein, expression, suggesting that it can act in trans to promote gene expression, albeit independently of MyoD protein. Yam-1 functions via cis regulation of miR-715, which in turn targets Wnt7b.…”
Section: Muscle-specific Lncrnas In Skeletal Muscle Developmentmentioning
confidence: 99%
“…44 Myolinc recruits TAR DNA-binding protein 43 (TDP-43) to the promoter of Filip1 to regulate its transcription in cis, and the Myolinc and TDP-43 complex binds to the promoters of muscle marker genes (eg, MyoD and Acta1) to promote differentiation and regeneration. 45 Overexpression of lncRNA MyoD upstream non-coding (MUNC) induced from a heterologous promoter increased endogenous MyoD, MyoG and Myh3 mRNA, but not protein, expression, suggesting that it can act in trans to promote gene expression, albeit independently of MyoD protein. 46 MUNC can also act as an enhancer RNA (eRNA) of MyoD.…”
Section: Muscle-specific Lncrnas In Skeletal Muscle Developmentmentioning
confidence: 99%